Bridging the digital divide for school students with Specific Learning Disability in India: A Systematic Literature Review - Preeti Sahrawat; Deepika Chamoli Shahi (International Journal of Education Sciences, 2025)
This systematic literature review aims to investigate the educational materials now utilized in inclusive classrooms in India to close the digital divide for children with specific learning disabilities (SLD). With an emphasis on policy, assistive technology, and teacher preparedness, the goal is to assess how well these resources work to create inclusive learning environments and look at how they might be tailored to help different learners. The review followed PRISMA criteria and used a three-stage methodological approach of identification, screening, and eligibility. The ERIC, PubMed, and DOAJ databases were searched using Boolean operators and phrase searches using terms such as "SLD," "digital divide," and "assistive technologies." After initial identification, 150 publications underwent screening according to inclusion criteria, including open-access availability, peer-reviewed works published within the last ten years, an examination of digital divide issues in India, and a focus on SLD students. A final set of 36 research was chosen following screening and eligibility evaluations, and each study's quality was guaranteed using the MMAT tool. In order to use digital educational tools for equitable learning opportunities in Indian classrooms, the aggregated findings offer a thorough assessment of current methods and pinpoint gaps, challenges, and best practices.
Keywords: LD; Learning disability; SLD; Specific Learning Disability; assistive technology; digital divide; literacy divide in India